Nanofabrication of Robust Nanoelectrodes for Electrochemical Applications - Dawson, K.; Strutwolf, J.; Herzog, G.; Arrigan, Damien; Quinn, A.; Riordan, A. (The Electrochemical Society, 2010)
Individual gold nanowire devices for use as nanoelectrodes in electrochemical studies were fabricated using a low-cost robust fabrication approach. Nanowires were characterized by a combination of direct electrical current-voltage measurements and cyclic voltammetry using the model analyte ferrocene monocarboxylic acid. We observed low electrical resistances to contacted nanowires and steady-state sigmoidal electrochemical voltammograms that may be described by classical Butler-Volmer kinetics. The potential of nanowires for use in future biosensing applications was explored by demonstrating mediated bioelectrocatalytic oxidation of glucose.